1998
DOI: 10.1111/j.1708-8305.1998.tb00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Mefloquine and Other Antimalarial Agents in the First Trimester of Pregnancy

Abstract: From the clinical data available, there is no indication that the risk of taking mefloquine in the first trimester of pregnancy is greater than that from any of the other antimalarials studied and the risk is considerably lower than that associated with falciparum malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 14 publications
1
39
0
Order By: Relevance
“…The majority (87.3%) of the abortion cases were reported by three publications. 6,23,24 The analysis by McGready et al found that the risk of spontaneous abortion was similar for woman treated with CQ (26%), quinine (27%), and artesunate (31%). The key finding is that even an episode of asymptomatic and symptomatic malaria can increase the risk for miscarriage by 2.7 times and four times, respectively, compared to women without malaria during pregnancy.…”
Section: Abortions/miscarriagesmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority (87.3%) of the abortion cases were reported by three publications. 6,23,24 The analysis by McGready et al found that the risk of spontaneous abortion was similar for woman treated with CQ (26%), quinine (27%), and artesunate (31%). The key finding is that even an episode of asymptomatic and symptomatic malaria can increase the risk for miscarriage by 2.7 times and four times, respectively, compared to women without malaria during pregnancy.…”
Section: Abortions/miscarriagesmentioning
confidence: 99%
“…24 Phillips-Howard et al showed from their analysis that MQ exposure resulted in a significant risk of therapeutically induced abortions compared with SP (26% compared with 7%, relative risk 1.32, 95% confidence interval 1.22-1.44). 23 …”
Section: Abortions/miscarriagesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they might be used for the treatment of uncomplicated malaria caused by CQ-resistant P. falciparum strains if no other treatment options are available, but only if the potential benefit is judged to outweigh the potential risks. Mefloquine has been reported to be safe for children and for pregnant women in the second and third trimester [25], but is associated with an increase of stillbirths in the first trimester [26] and is thus not recommended during pregnancy [16].…”
Section: Treatment Of Benign Plasmodium Falciparum Infectionsmentioning
confidence: 99%